2012
DOI: 10.1038/ki.2012.137
|View full text |Cite
|
Sign up to set email alerts
|

Multifactorial intervention with nurse practitioners does not change cardiovascular outcomes in patients with chronic kidney disease

Abstract: Strict implementation of guidelines directed at multiple targets reduces vascular risk in diabetic patients. Whether this also applies to patients with chronic kidney disease (CKD) is uncertain. To evaluate this, the MASTERPLAN Study randomized 788 patients with CKD (estimated GFR 20-70 ml/min) to receive additional intensive nurse practitioner support (the intervention group) or nephrologist care (the control group). The primary end point was a composite of myocardial infarction, stroke, or cardiovascular dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
114
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(121 citation statements)
references
References 45 publications
(42 reference statements)
4
114
0
1
Order By: Relevance
“…34 In a comparison between additional intensive nurse-practitioner support and nephrologist care, the blood pressure decrease in the intervention group was 3/2 mmHg more (P<0.001) than in the control group. 35 However, in a randomised trial in which patients were randomly assigned to a nurse-coordinated team in secondary care, or to usual care in general practice, no effect on cardiovascular risk-factor control or on clinical end points was found. 36 The opportunity to ask advice from a nephrologist has been studied in a shared care system in the UK.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…34 In a comparison between additional intensive nurse-practitioner support and nephrologist care, the blood pressure decrease in the intervention group was 3/2 mmHg more (P<0.001) than in the control group. 35 However, in a randomised trial in which patients were randomly assigned to a nurse-coordinated team in secondary care, or to usual care in general practice, no effect on cardiovascular risk-factor control or on clinical end points was found. 36 The opportunity to ask advice from a nephrologist has been studied in a shared care system in the UK.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…10 In short, during the follow-up in the study, all events were adjudicated by an independent committee. Myocardial infarction was defined as acute chest pain or tightness, accompanied by evident and lasting new ischemic changes on an ECG or an established rise and fall pattern of cardiac enzymes.…”
Section: End Pointsmentioning
confidence: 99%
“…Design, rationale, and main findings of the study have been described in detail previously. [9][10][11] In short, CKD patients with an estimated creatinine clearance of 20 to 70 mL/min per 1.73 m 2 aged >18 years were included. Patients were randomized to a multifactorial approach for risk factor management by a nurse practitioner added to nephrologist care or to usual care by a nephrologist alone.…”
Section: Multifactorial Approach and Superior Treatment Efficacy In Rmentioning
confidence: 99%
“…12,13 We recently showed that intensified support by nurse practitioners also improved risk factor levels in patients with CKD. 14,15 However, the intervention did not significantly reduce the rate of cardiovascular events. 15 In this analysis, we evaluated the effect of the intervention on renal endpoints after extended follow-up.…”
mentioning
confidence: 99%
“…14,15 However, the intervention did not significantly reduce the rate of cardiovascular events. 15 In this analysis, we evaluated the effect of the intervention on renal endpoints after extended follow-up.…”
mentioning
confidence: 99%